Do Adolescents Who Live or Go to School Near Fast Food Restaurants Eat More Frequently From Fast Food Restaurants? - Forsyth, Ann (2012)
This population-based study examined whether residential or school neighborhood access to fast food restaurants is related to adolescents’ eating frequency of fast food. A classroom-based survey of racially/ethnically diverse adolescents (n=2,724) in 20 secondary schools in Minneapolis/St. Paul, Minnesota was used to assess eating frequency at five types of fast food restaurants. Black, Hispanic, and Native American adolescents lived near more fast food restaurants than white and Asian adolescents and also ate at fast food restaurants more often. After controlling for individual-level socio-demographics, adolescent males living near high numbers fast food restaurants ate more frequently from these venues compared to their peers.